Pathologic complete response to TNT + camrelizumab for rectal cancer with surgical anus-preservation: case report and literature review - Pi, Feng; Tang, Gang; Xie, Chaozheng; Cao, Yukun; Yang, Shilai; Wei, Zhengqiang (Frontiers in Surgery, 2023)
7.Background:This case report demonstrates the efficacy of total neoadjuvant therapy (TNT) based on pathological complete response (PCR). We also discuss the surgical approach to preserving the anus and its perioperative management. 8.Case Presentaion:The patient was a 26-year-old woman, with blood in the stool and stool thinning for over two months. Preoperative examination revealed locally advanced rectal cancer invading the left anal raphe and enlarged lymph nodes adjacent to the left internal iliac vessels. The lesion was preoperatively classified as T4bN1bM0 IIIC. Considering the size and depth of the tumor, it was difficult to have sufficient margins for radical resection, and the tumor was too close to the anal orifice. Considering the patient's youth and strong desire to preserve the anus, it was decided to use TNT combined with a camrelizumab regimen. After the entire course of neoadjuvant radiotherapy, the tumor size significantly reduced in fibrotic manifestations, and no enlargement of the lymph nodes adjacent to the left internal iliac vessels was observed. She underwent robotic laparoscopic ultra-low anterior rectal resection, left lateral lymph node dissection, and temporary ileostomy, and no significant residue was observed after all bowel tubes were taken for examination, nor was there cancerous involvement at the distal or radial cut edges, or metastasis. The patient was discharged nine days postoperatively, and no major complications were detected. Follow-up was performed without adjuvant chemotherapy. 9.Conclusions：TNT may be a better surgical option for preserving the anus and for complete radical resection in patients with LARC for whom Miles’ resection is indicated.